Analysis Of High Speed Shear Slitting Machine Based On Cutting Force, Temperature And Cutting Speed - Ab Wahab, Norfariza (Asian Research Publishing Network (ARPN), 2019)
High speed machining is well known in manufacturing world and it is one of the most demanding process in every industry today. Almost every factory in this world using this process in order to make their product better in every aspect.This study is for high speed shear slitting process which is one of the oldest method in shearing process and it will have focused for academic purpose. Although there are many methods such as laser cut, plasma cut and waterjet available but there is some problem occurred such as high cost, maintenance, and chip formation. The new model of high speed shear slitting prototype will be tested by simulation to evaluate cutting forces, temperature and cutting speed. The result is the parameter of the analysis can be analyzed. The conclusion is the shear slitting process can be invented from industry use and can be used for academic purpose.